Patient Attitudes and Their Awareness Towards Skin Cancer-Related Apps: Cross-Sectional Survey - Steeb, Theresa; Wessely, Anja; Mastnik, Sebastian; Brinker, Titus Josef; French, Lars Einar; Niesert, Anne-Charlotte; Berking, Carola; Heppt, Markus Vincent (JMIR Publications, 2019)
BackgroundIn the emerging era of digitalization and electronic health, skin cancer-related apps represent useful tools to support dermatologic consultation and examination. Yet, little is known about how patients perceive the value of such apps. ObjectiveThe aim of this study was to investigate patient attitudes and their awareness toward skin cancer-related apps. MethodsA cross-sectional study including 200 patients from the oncological outpatient unit was conducted at the University Hospital (LMU Munich, Germany) between September and December 2018. Patients were asked to complete a self-administered questionnaire on the popularity and usefulness of health-related and skin cancer-related apps. A descriptive analysis was performed with the expression of categorical variables as frequencies and percentages. For continuous variables, the median and range were indicated. Contingency tables and chi-square tests were performed to investigate associations between sociodemographic data and selected items of the questionnaire. ResultsA total of 98.9% (195/197) of patients had never used skin cancer-related apps or could not remember. In 49.7% (93/187) of cases, patients were unsure about the usefulness of skin cancer apps, whereas 42.6% (78/183) thought that skin cancer apps could supplement or support the professional skin examination performed by a physician. However, 47.9% (90/188) were interested in acquiring more information by their dermatologists about skin cancer apps. Young age (P=.002), male gender (P=.02), a previous history of melanoma (P=.004), and higher educational level (P=.002) were significantly associated with a positive attitude. Nevertheless, 55.9% (105/188) preferred a printed patient brochure on skin cancer to downloading and using an app. ConclusionsThe experience and knowledge of skin cancer-related apps was surprisingly low in this population, although there was a high general interest in more information about such apps. Printed patient brochures were the preferred information source.